2017
DOI: 10.1186/s12881-017-0409-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel NPC1 mutations with different segregation in two related Greek patients with Niemann-Pick type C disease: molecular study in the extended pedigree and clinical correlations

Abstract: BackgroundNiemann-Pick type C disease (NPC) is an autosomal recessive, neurovisceral, lysosomal storage disorder with protean and progressive clinical manifestations, resulting from mutations in either of the two genes, NPC1 (~95% of families) and NPC2. Contrary to other populations, published evidence regarding NPC disease in Greece is sparse.MethodsThe study population consisted of two Greek NPC patients and their extended pedigree. Patients’ clinical, biochemical, molecular profiles and the possible correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Distribution of mutations in the two studied amino acid residues (855-1098 and 1038-1253)was consistent with the previously described [34], [35]; moreover, a recent Egyptian study showed that around 37% of detected mutant alleles were in the currently studied hotspot regions [31], confirming that they can also be considered as hot spot regions in NPC Egyptian patients. Although the missense mutations p.Ile1061Thr, p.Arg1186His, p.Pro1007Ala, and Gly992Trp were previously reported as the most common NPC mutations [9], none of them were detected in the present study;however, p.Ile1061Thr was reported in the heterozygous state coupled with p.Ser627Arg in an Egyptian patient with the late infantile onset of disease [31]. Among severely affected patients, we identified one nonsense homozygous mutation, p.Arg958* inpatient9 led to protein truncation in exon 19 within the cysteine-rich luminal loop between TM8 and 9.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Distribution of mutations in the two studied amino acid residues (855-1098 and 1038-1253)was consistent with the previously described [34], [35]; moreover, a recent Egyptian study showed that around 37% of detected mutant alleles were in the currently studied hotspot regions [31], confirming that they can also be considered as hot spot regions in NPC Egyptian patients. Although the missense mutations p.Ile1061Thr, p.Arg1186His, p.Pro1007Ala, and Gly992Trp were previously reported as the most common NPC mutations [9], none of them were detected in the present study;however, p.Ile1061Thr was reported in the heterozygous state coupled with p.Ser627Arg in an Egyptian patient with the late infantile onset of disease [31]. Among severely affected patients, we identified one nonsense homozygous mutation, p.Arg958* inpatient9 led to protein truncation in exon 19 within the cysteine-rich luminal loop between TM8 and 9.…”
Section: Discussionmentioning
confidence: 96%
“…p.Pro1007Ala is reported as the second most recurrent mutationin different populations, especially in Germany. p.Arg1186His is widely distributed inthe Czech, while Gly992Trp is individualized to Nova Scotian patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is worth noting that patient NPC/ 1 who had no AGSA prior to treatment and a rather limited positivity after its initiation, apart from slight clumsiness and minor impairment in the motor coordination at all developmental stages, remains free of neurological manifestations at the age of 11 years. Patient NPC/5, already showing neurological deficit when treatment was initiated, showed a stabilization of her clinical picture, whereas patient NPC/2 showing an early onset severe disease died approximately one year after the initiation of treatment [ 22 , 23 ] . SFB syndrome or mucopolysacharidosis IIIB, is a disorder with severe neurological manifestations characterized by the accumulation of partially degraded heparan sulphate oligosaccharides in tissues as well as the secondary storage of gangliosides and cholesterol [ 24 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The age of onset ranges from early infancy to an adolescent/adult onset corresponding to the estimated lifespan ranging from a few days to about 60 years [ 15 , 16 ]. To date, over 400 NPC1 mutations are known ( ) [ 17 , 18 , 19 ]. The most common mutation, I1061 T, correlates with the classical juvenile phenotype, frequently found in patients with Western European descent or in Hispanic patients who originated from the Upper Rio Grande Valley in the U.S.A.…”
Section: Introductionmentioning
confidence: 99%